Enhancement of emission currents in plasma electron sourcesbased on a low-pressure arc discharge; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Koval T. V. Tamara Vasilievna (2015, 2015)
Title screen